1997
DOI: 10.1074/jbc.272.3.1742
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hypothermia-induced Cellular Stress Response in Mouse Tissues

Abstract: Cells respond to adverse environmental conditions by expressing heat shock proteins, which serve to protect cells from harmful effects of the stress conditions. In this study we demonstrated that mice subjected to whole body hypothermia induced the cellular stress response, resulting in the increased expression of hsp72 mRNA in brain, heart, kidney, liver, and lung. We performed a detailed analysis of the major parameters of the stress response and found that cold induction of hsp expression is mediated by hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 30 publications
3
44
0
Order By: Relevance
“…The combined treatment of GA and MPTP further increased Hsp70-HSE binding in the striatum when compared with groups pretreated with GA alone or treated with MPTP alone. The HSE binding, using the self-complementary HSE consensus oligonucleotide (5Ј-CTAGAAGCTTCTA-GAAGCTTCTAG-3Ј) (48), also showed a similar pattern of enhancement of HSE binding in the striatum of GA pretreated, MPTP-treated, or combined treated mice (data not shown). .…”
Section: Ga Pretreatment and Mptp Treatment Enhanced Hse Binding To Tmentioning
confidence: 69%
“…The combined treatment of GA and MPTP further increased Hsp70-HSE binding in the striatum when compared with groups pretreated with GA alone or treated with MPTP alone. The HSE binding, using the self-complementary HSE consensus oligonucleotide (5Ј-CTAGAAGCTTCTA-GAAGCTTCTAG-3Ј) (48), also showed a similar pattern of enhancement of HSE binding in the striatum of GA pretreated, MPTP-treated, or combined treated mice (data not shown). .…”
Section: Ga Pretreatment and Mptp Treatment Enhanced Hse Binding To Tmentioning
confidence: 69%
“…Cullen and Sarge (1997) reported that hypothermia elevated hsp 72 mRNA expression in the brain, heart, kidney, liver and lungs of mice. On the contrary, Matz et al (1995) noted hsp induction in the brown adipose tissue of cold-stressed mice but not in the brain, heart and lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Cells subjected to a nonlethal heat shock increase cellular HSP70 levels, and those levels correlate with a transient resistance to higher, normally lethal temperatures (29). A review of results suggests that inactivation of either of the two genes (Hsp70.1 and Hsp70.3) results in deficient maintenance of acquired thermotolerance and increased sensitivity to heat stress-induced apoptosis (8,19,27). The synthetic or protein rescue functions of HSP70 are counterbalanced by participation in the ubiquitin pathway that clears the cell of unstable or damaged proteins by proteosome degradation (2).…”
Section: Discussionmentioning
confidence: 99%